Pressure Sensitivity of Streptococcal Growth in Relation to Catabolism - Marquis, Robert E. (1971)
The sensitivity of Streptococcus faecalis growth to hydrostatic pressures ranging up to 550 atm was found to depend on the source of adenosine triphosphate for growth. Barotolerance of cultures growing in a complex medium with ribose as major catabolite appeared to be determined primarily by the pressure sensitivity of ribose-degrading enzymes. Apparent activation volumes for growth were nearly identical to those for lactate production from ribose, and yield coefficients per mole of ribose degraded were relatively independent of pressure. In contrast, cultures with glucose as main catabolite were less sensitive to pressure; glycolysis was less severely restricted under high pressure than was growth, and yield coefficients declined with pressure, especially above 400 atm. Thus, two distinct types of barotolerance could be defined—one dominated by catabolic reactions and one dominated by noncatabolic reactions. The results of experiments with a series of other catabolites further supported the view that catabolic reactions can determine streptococcal barotolerance. We also found that growing, glucose-degrading cultures increased in volume under pressure in the same manner that they do at 1 atm. Thus, it appeared that the bacterium has no alternative means of carrying out glycolysis under pressure without dilatation. Also, the observation that cultures grown under pressure did not contain abnormally large or morphologically deformed cells suggested that pressure did not inhibit cell division more than cell growth.